2012
DOI: 10.4314/ijbcs.v6i1.33
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of <em>Thymelaea hirsuta</em> and protective effect against CCl<sub>4</sub>-induced hepatic injury in rats

Abstract: The aerial part of Thymelaea hirsuta (TH) is used as decoction in the treatment of different pathologies in folk medicine in Morocco. The present investigation was carried out to evaluate the potential of toxicity of an aqueous extract of TH and its hepatoprotective activity against CCl 4 -induced hepatic injury in rats. In the acute study, there were no signs of toxicity observed after oral administration of single dose of the extract (5 g/kg body weight). In the sub-chronic dose study, (given by gavages (4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Measurement of these enzymes is significant in clinical and toxicological studies as changes in their activities are indicative of tissue damage by toxicants. The increase in serum level of these enzymes might be due to their leakage out of the tissues into the blood system due to destruction of their cellular membranes (Azza et al, 2012). Exposure to chemical compounds may result into significant changes in the structure, function, metabolic transformation and concentration of biomolecules, enzymes and even metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of these enzymes is significant in clinical and toxicological studies as changes in their activities are indicative of tissue damage by toxicants. The increase in serum level of these enzymes might be due to their leakage out of the tissues into the blood system due to destruction of their cellular membranes (Azza et al, 2012). Exposure to chemical compounds may result into significant changes in the structure, function, metabolic transformation and concentration of biomolecules, enzymes and even metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous extract was screened for alkaloids, flavonoids, tannins, and saponins as described before 14,15 . Tests were based on the visual observation of color changes or formation of a precipitate after the addition of specific reagents.…”
Section: Preliminary Phytochemical Screeningmentioning
confidence: 99%
“…(Quezel et Santa 1963). Previous studies showed that T. hirsuta has no toxic effects on humans (Bnouham et al 2007;Azza et al 2012). Various parts of T. hirsuta have been widely used in the paper industry (Schmidt et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, T .hirsuta is used as antiseptic, anti-inflammatory and in the treatment of hypertension (Le Floc'h 1983;Azza et al 2012;Bnouham et al 2012;Azza and Oudghiri 2015). It is also used in hypoglycemic, antidiabetic drugs and as an antioxidant (Ziyyat et al 1997;Djeridane et al 2006;El Amrani et al 2009;Akrout et al 2011;Trigui et al 2013;Yahyaoui et al 2017, 2018a and.…”
Section: Introductionmentioning
confidence: 99%